PENGARUH KEPEMIMPINAN SPIRITUAL TERHADAP KEPUASAN KERJA PADA PT. BANK SYARIAH MANDIRI KC MANADO - ANDREW M. M. TUMIMBANG; William A. Areros; Riane J. Pio (JURNAL ADMINISTRASI BISNIS, 2017)
Spiritual Leadership is a leader who can apply spiritual values intothe practice of daily leadership. job satisfaction is a set of employee feelingsabout the fun or the absence of their work. The purpose of this study is todetermine the influence of spiritual leadership on job satisfaction at PT.Bank Syariah Mandiri KC Manado. Methods of data collection usingquestionnaires and interviews. Analytical tool is the product momentcorrelation and simple linear regression to know the correlation or influenceof the variable. The result of correlation shows the relationship of spiritualleadership to job satisfaction is moderate. However, hypothesis testing showsthere is a positive influence between spiritual leadership and job satisfaction.Simple regression results show leaders have a spiritual leadership thatimpact on employee job satisfaction. The conclusion that can be taken fromthis research is there is positive and significance influence between spiritualleadership with job satisfaction at PT. Bank Syariah Mandiri KC Manado.The advice of this research is to always maintain the spiritual leadership of aleader because it is proven to increase job satisfaction from employees.Key : spiritual leadership, Job Satisfaction